2016
DOI: 10.1080/07317115.2016.1215365
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease and Driving Cessation: a Journey Influenced by Anxiety

Abstract: Implications of the study findings are outlined and aim to provide information about the needs to enable future clinical directions to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Extensive research examines elderly people and the consequences of driving license withdrawal, such as social exclusion (e.g., [7,39]), depression (e.g., [20]), and reduced independence (e.g., [1]). Similar results have been found in studies of people with impairments and license withdrawal (e.g., [24,29,35]).…”
Section: Introductionsupporting
confidence: 88%
“…Extensive research examines elderly people and the consequences of driving license withdrawal, such as social exclusion (e.g., [7,39]), depression (e.g., [20]), and reduced independence (e.g., [1]). Similar results have been found in studies of people with impairments and license withdrawal (e.g., [24,29,35]).…”
Section: Introductionsupporting
confidence: 88%
“…While driving anxiety has been self-reported by older adults in the general population [30], the current study is only the second qualitative study to report driving anxiety among individuals with PD [8]. There remains, however, some equivocation within the literature as to whether or not driving anxiety in older adults is predictive of on-road safety.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research has suggested that voluntary driving cessation may be related to the availability of alternative transportation [23] and also suggests that a lack of discussion prior to driving cessation can lead to a sudden (and involuntary) loss of license [24]. Not surprisingly, involuntary loss of license has been shown in previous research to be a traumatic experience, due to an abrupt loss of independence and sense of identity [8, 24]. Thus, the development of adequate alternative transportation solutions would benefit individuals with PD and could facilitate transition from “driving cessation,” perceived by participants as a problematic transition and towards “driving retirement,” a process of pre-emptive and person-centred planning for positive transitions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations